Lipid nanoparticle-based co-delivery of epirubicin and BCL-2 siRNA for enhanced intracellular drug release and reversing multidrug resistance. (17th February 2018) - Yu, Miao; Han, Shangcong; Kou, Zhongai; Dai, Jialing; Liu, Jiao; Wei, Chen; Li, Yitong; Jiang, Lutao; Sun, Yong
Abstract: At present, combined therapy has become an effective strategy for the treatment of cancer. Co-delivery of the chemotherapeutic drugs and siRNA can more effectively inhibit tumor growth by nano drug delivery systems (NDDSs). Here, we prepared and evaluated a multifunctional envelope-type nano device (MEND). This MEND was a kind of composite lipid-nanoparticles possessing both the properties of liposomes and nanoparticles. In this study, an acid-cleavable ketal containing poly (β-amino ester) (KPAE) was used to bind siBCL-2 and the KPAE/siBCL-2 complexes were further coated by epirubicin (EPI) containing lipid to form EPI/siBCL-2 dual loaded lipid-nanoparticles. The results showed that the average size of EPI/siBCL-2-MEND was about 120 nm, and the average zeta potential was about 41 mV. The encapsulation efficiency (EE) of EPI and siBCL-2 was 86.13% and 97.07%, respectively. EPI/siBCL-2 dual loaded lipid-nanoparticles showed enhanced inhibition efficiency than individual EPI-loaded liposomes on HepG2 cells by MTT assay. Moreover, western blot experiment indicated co-delivery of EPI/siBCL-2 can significantly down-regulate the expression of P-glycoprotein (P-gp), while free EPI and EPI-loaded liposomes up-regulated it. Therefore, the strategy of co-delivering EPI and siBCL-2 simultaneously by lipid-nanoparticles showed promising potential in reversing multidrug resistance of tumor cells.